Nutrients in Two and Three Cotyledon Seedlings of Peganum harmala L. Under Soil Salinity - Narantsetseg Amartuvshin (Mongolian Journal of Biological Sciences, 2013)
The fi nal seed germination of Peganum harmala L. was signifi cantly decreased at soil salinity of 2.6, 8.6 and 10.8 DS/m, compared with adequate concentration. Fe content in three cotyledon seedlings was signifi cantly correlated with the percentage of fi nal seed germination (rs = 0.94, P= 0.0048), under different concentrations of soil salinity. Normal nutrient order (in two cotyledon seedlings) changed at 10.8 DS/m of soil salinity. Two cotyledon seedlings adapted in the increasing concentrations of soil salinity better than three cotyledon seedlings. Three cotyledons are associated with iron defi ciency and can result of Fe-defi ciency at least during embryogenesis. The results indicate that the variation in cotyledon number of P. harmala L. is related with soil salinity, resulting in at least Fe defi ciency.